A cross sectional study on immunization status of anganwadi children in a rural area of north Kerala, India - S. V., Rajeev; K. V., Radhamani (International Journal of Research in Medical Sciences, 2017)
Background: The current scenario depicts that immunization coverage has been steadily increasing but the average level remains far less than the desired. Though there is increased accessibility of health care services in rural areas, its utilization is low. Hence the present study is undertaken in an attempt to assess immunization status of children between 2 to 5 years of age enrolled in anganwadi centers in a field practice area of Pariyaram Medical College. The aim of the study was to assess the immunization status of anganwadi children in a rural area of north Kerala, India. Methodology: A cross Sectional Study was done among anganwadi Children between ages 2 to 5 years from January 2013 to March 2013 at Cheruthazham. Cluster sampling method was used. Each Anganwadi centre was considered as a single cluster and all children from the selected anganwadi centers were included in the study. Data was analyzed by SPSS Version 17, Microsoft excel 2007. Results: 94% of children were fully immunized with BCG, DPT, OPV and measles. Coverage was highest for BCG, DPT-1 and OPV-1 (100%) and least for measles, 94%. The major cause of incomplete immunization was postponement of immunization due to inter current illness of the child. There is only marginal difference in immunization coverage according to gender, religion or education of parents. Conclusion: Regular health education sessions, and regular reminders and removal of misconceptions prevailing among people will solve the problems of non-immunization.